Relative instability ratios of bone wall defects in trochanteric hip fractures: A finite element analysis - Yang, Ao-Lei; Mao, Wei; Chang, Shi-Min; Dong, You-Hai (Frontiers in Bioengineering and Biotechnology, 2023)
Background: For decades, medial and lateral wall fragments of trochanteric hip fractures were considered two pivotal factors that would influence the stability of postoperative femur-implant complex. However, most studies seemed to misunderstand a concept of the posteromedial fragment and equated it with the medial wall, which overlooked vital roles of the anteromedial wall. Besides, roles of the posterior coronal bone fragment were also highlighted in some research. Hence, influences of the bone walls above on the trochanteric fracture instability are yet to be investigated and quantified by means of finite element analysis. Methods: Eight trochanteric fracture fixation models with the different wall defects were constructed. Besides, outcome indicators were set as the von Mises stress of the implant models, the maximum/minimum principal strain, the risky tensile/compressive volume and the volume ratios of the bone models, the femoral head vertex displacement and the fracture surface gap. Based on these indicator values, the relative instability ratios were computed. Results: Outcome indicators absolute values and nephograms of all model showed the same upward and concentrating trends with exerted hip contact loads shifting from static walking to dynamic climbing. Similarly, these indicators also exhibited the same trends when the models solved in sequence of these eight models. Moreover, the relative instability ratio of the medial wall (100%), particular the anteromedial part (78.7%), was higher than the figure for the lateral wall (36.6%). Conclusions: It was the anteromedial wall that played the relatively pivotal stabilizing roles in trochanteric hip fractures compared with the posteromedial wall and the lateral wall, which indicated that orthopaedic surgeons should attach more importance to the anteromedial cortex support in an operating theatre.